Riba (Interest) Between Reason and Revelation in Islam - Saheed Afolabi Ashafa (Journal of Islamic Economic and Business Research, 2021)
This paper discussed the opposing views of Reason (human intellect) and Revelation (Islamic thought) on the concept and practice of Ribá¾± (interest). As it is known that ribá¾± is a universal instrument engaged for economic practices, while revelation, particularly Islam, prohibits it. In this study, arguments from both thoughts are placed side by side using primary and secondary sources. In this regard, the study adopted a descriptive qualitative research design for elucidation. It examined and established the relationship between reason and revelation as well as the areas of departure from each other. The study found out that riba-based economic practice has not been favorable to the course of development across the globe, hence the frequent shift from higher to lower interest rates by various countries. Consequently, Islamic alternatives to ribá¾± were presented with a view to safeguarding the faith and socio-economic status of the adherents of Islam. Research-based recommendations were offered for necessary adjustment by stakeholders. Optimistically, the submission of this study will stimulate a positive response from the stakeholders.